AI-Driven Personalized Design: Adapting Building Interior Design Based on User Preferences - Irwan, Dede (International Journal of Artificial Intelligence Research, 2025)
The adoption of Artificial Intelligence (AI) increases efficiency in the design industry. However, the implementation of AI is not entirely received positively by designers. This study aims to explore the application of AI technology in personalizing building interior design based on user preferences. A qualitative approach was employed using the design thinking method. Data were collected through in-depth interviews with product and graphic designers and subsequently validated by experts in the field of AI. The results of this study indicate that the integration of AI in interior design based on user preferences can assist designers in generating more personalized, efficient, and client-specific design recommendations. AI has proven capable of processing both explicit and implicit preference data to predict optimal layouts, color selections, materials, and lighting. However, this study also found several significant challenges, such as inconsistent data quality, limitations of algorithms in understanding subjective and emotional aspects, and concerns regarding user data privacy. Nonetheless, the use of AI in interior design still offers great opportunities to create spaces that are more functional, innovative, and adaptive to the evolving lifestyles of their occupants.